Strategi pembelajaran literasi dan numerasi menggunakan media papan membaca dan papan pintar untuk meningkatkan minat belajar Siswa SDN 012 Rambah Hilir - Ulfia Hasanah; M. Janrigo Hidayat; Husnul Khotimah; Intan Almadina; Nurul Azkiah; Putri Aulia Ramadani; Darryandra Arshaff; Putri Ramadani; Helmi Helmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Learning Media is everything that can be used to convey messages or information in the teaching and learning process so that it can stimulate students' attention and interest in learning. The problem found at SDN 012 is the limited learning media in supporting the teaching and learning process so that it causes children's development and understanding to be less than optimal, such as children having difficulty in recognizing the alphabet and understanding mathematics lessons. This Kukerta activity aims to help students at SDN 012 Pasir Utama Village in recognizing the letters of the alphabet and understanding the divisional material taught in schools. Smart Board and Reading Board Learning Media are strategies used to make it easier for students and students to understand and improve their knowledge. Smart Board media is used in division materials that aim to make it easier for grade 4 students of SDN 012 Rambah Hilir to understand mathematical sciences, especially in division, while reading boards aim to help students, especially grade 1, in alphabet letter recognition and word-to-word spelling.